1990
DOI: 10.1128/jcm.28.7.1591-1596.1990
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two groups of Mycobacterium paratuberculosis strains by restriction endonuclease analysis and DNA hybridization

Abstract: Genomic DNA was prepared from four reference strains of Mycobacterium paratuberculosis and 46 isolates of this organism from New Zealand, Australia, Canada, and Norway and also from two mycobactin-dependent "wood pigeon" strains. The DNA was characterized by restriction endonuclease analysis, both with and without DNA hybridization, with a probe specific to a repetitive DNA sequence in M. paratuberculosis. Both techniques differentiated M. paratuberculosis strains into two groups, but DNA hybridization reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
3
14

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(123 citation statements)
references
References 22 publications
6
100
3
14
Order By: Relevance
“…The initial efforts to type MAP strains using the IS900 element also occurred at this time. Genomic DNA was extracted and subjected to BstEII restriction enzyme digestion with the resulting fragments separated out by electrophoresis on long agarose gels to detect distinct banding patterns (Collins et al 1990;Whipple et al 1990). Whilst sheep and cattle strains were long observed to be phenotypically different in growth rate and appearance, these experiments showed, for the first time, a genetic difference between these two classes.…”
Section: History Of Map Strain Typingmentioning
confidence: 99%
“…The initial efforts to type MAP strains using the IS900 element also occurred at this time. Genomic DNA was extracted and subjected to BstEII restriction enzyme digestion with the resulting fragments separated out by electrophoresis on long agarose gels to detect distinct banding patterns (Collins et al 1990;Whipple et al 1990). Whilst sheep and cattle strains were long observed to be phenotypically different in growth rate and appearance, these experiments showed, for the first time, a genetic difference between these two classes.…”
Section: History Of Map Strain Typingmentioning
confidence: 99%
“…4 The use of REA and RFLP using B s t EII indicated that there we re two major groups of M para t u b e rc u l o s i s in isolates that originated mostly from New Ze a l a n d . 5 These we re called cattle (C) and sheep (S) strains because of the predominance of the species from which they originated and were differentiated by the presence (in C strains) or absence of IS900 within a Bst EII digested 1.6 kb fragment. The RFLP method identified more differences within the larger groups than previous REA studies.…”
mentioning
confidence: 99%
“…The isolation of yellow colonies of M. paratuberculosis from samples of 3 sheep, similar to the variant isolated by TAYLOR (1951) from sheep in Scotland and Iceland, supposes the involvement of different strains in Morocco. Further investigations based on molecularbiological techniques, e. g. by using IS900, an insertion element specific for M. paratuberculosis (GREEN et al, 1989;VARY et al, 1990), might contribute to clarification of genetic strain differences (COLLINS et al, 1990;DE LISLE et a]., 1992; THORESEN and OLSAKER, 1994), as well as improving rapid diagnosis of the disease and identification of M. paratuberculosis. Studies applying the polymerase chain reaction (PCR) directly to fecal samples have already been carried out in cattle (WHIPPLE et al, 1992;COLLINS et al, 1993b;BLEUMINK-PLUYM et al, 1994;CHALLANS et al, 1994) and sheep (COLLINS et al, 1993a;, and the reports show that, by this technique, the detection of M. paratuberculosis could be accomplished within 2-3 days.…”
Section: Resultsmentioning
confidence: 99%
“…A possible existence of sheep-associated strains of M . paratuberculosis, likely to have unique growth requirements, has been suggested (GUNNERSSON, 1979;CARRIGAN and SEAMAN, 1990;COLLINS et al, 1990), and even a demand for media different from those used for the culture of bovine strains has been proposed (JUSTE et al, 1991).…”
Section: Discussionmentioning
confidence: 99%